Assessing Taxpayer Compliance Using Segmentation: A Case Study of KPP Pratama Jakarta Sawah Besar Dua - Khadafi, Muammar; Martani, Dwi (E-Jurnal Akuntansi; Vol 34 No 8 (2024), 2024)
To enhance the supervisory function over taxpayers and improve tax revenue and compliance, the Directorate General of Taxes (DGT) issued SE-05/PJ/2022 on Taxpayer Compliance Supervision, refining the earlier SE-07/PJ/2020. A key provision of this regulation introduces the segmentation of taxpayers at the Primary Tax Office level. This study evaluates the implementation of taxpayer supervision through the segmentation method. A qualitative research approach was employed, using a case study at KPP Pratama Jakarta Sawah Besar Dua. The evaluation framework was based on criteria established by the OECD (2021), including relevance, coherence, effectiveness, efficiency, impact, and sustainability. The findings indicate that the taxpayer supervision policy utilizing the segmentation method aligns with the needs of the tax office in optimizing its supervisory role. The policy is consistent with broader tax regulations and aligns with policies implemented by other agencies. Furthermore, it has been effectively and efficiently executed, contributing positively to increased tax revenue and compliance while demonstrating sustainability. Given these outcomes, the continuation and further enhancement of this policy are recommended. Keywords: Policy Evaluation, Supervision, Segmentation, OECD Criteria